Performance analysis of smart optimization antenna for wireless networks - Jacob Abraham; Kannadhasan Suriyan; Beulah Jackson; Mahendran Natarajan; Thanga Mariappan Lakshmanaperumal (International Journal of Electrical and Computer Engineering (IJECE), 2023)
Antenna design has significantly advanced as a result of the widespread need for wireless communications and data substitution through wireless devices. The research article's goal is to provide a conceptual framework, difficulties, and opportunities for a source as well as a general overview of the antenna used in wireless communications applications. In this proposed research, we will go over a variety of topics related to mobile communication and fifth generation (5G) technologies, including its pros and benefits. A thorough comparison between the expected properties of the antennas and each generation, from 1st generation (1G) to 5G, is also included. This article also provides an overview of the investigated 5G technologies and various antenna designs.